PENGARUH TINGKAT KESEHATAN BANK MELALUI METODE RGEC, SUSTAINABILITY REPORT, COMPANY SIZE TERHADAP COMPANY VALUE PADA PERUSAHAAN PERBANKAN BUMN TAHUN 2021-2023 - Muhammad Nabil Bouxit; Baldric Siregar; Frasto Biyanto; Miswanto, Miswanto (Bajang Institute, 2025)
This study aims to analyze the effect of Bank Health Level using the RGEC method, Sustainability Report, and Company Size on Firm Value in state-owned banking companies listed on the Indonesia Stock Exchange (IDX) during the period 2021-2023. The secondary data used includes financial reports and sustainability reports from four state-owned banking companies selected through purposive sampling method. The analysis was carried out using SPSS software with classical assumption tests, descriptive statistical tests, and multiple linear regression. The results showed that Bank Health Level has a negative and insignificant effect on Firm Value, Sustainability Report has a significant positive effect on Firm Value, while Company Size has a negative and insignificant effect on Firm Value.